Distal Chevron Osteotomy Increases Anatomic Intermetatarsal Angle in Hallux Valgus. Issue 4 (14th October 2020) - Chan, Jeremy Y.; Noori, Naudereh; Chen, Stephanie; Pfeffer, Glenn B.; Charlton, Timothy P.; Thordarson, David B.
Background: Distal chevron metatarsal osteotomy (DCO) is a common technique to address hallux valgus (HV), which involves coronal translation of the capital fragment resulting in a nonanatomic first metatarsal. The purpose of this study was to evaluate the radiographic effect of the DCO on the anatomic vs the mechanical axis of the first metatarsal. Our hypothesis was that patients undergoing DCO would have improvement in the mechanical metatarsal axis but worsening of the anatomic axis. Methods: This was a retrospective case series of consecutive patients who underwent DCO for HV. The primary outcomes were the change in anatomic first–second intermetatarsal angle (a1-2IMA) vs mechanical first–second intermetatarsal angle (m1-2IMA). Secondary outcomes included the change in hallux valgus angle (HVA) and medial sesamoid position. Results: 40 feet were analyzed with a mean follow-up of 21.2 weeks. The a1-2IMA increased significantly (mean, 4.1 degrees) whereas the m1-2IMA decreased significantly (mean, 4.6 degrees) following DCO. There was a significant improvement in HVA (mean, 12.5 degrees). Medial sesamoid position was improved in 21 feet (52.5%). Patients with no improvement in sesamoid position were found to have a larger increase in a1-2IMA (mean, 4.7 vs 3.5 degrees, P = .03) and less improvement in m1-2IMA (mean, 3.8 vs 5.2 degrees, P = .02) compared to patients with improvement in sesamoid position. Conclusion: Distal chevron osteotomy for HV was associated with worsening of the anatomic axis of the first metatarsal despite improvements in the mechanical metatarsal axis, HVA, and medial sesamoid position. Greater worsening of the anatomic axis was associated with less improvement of sesamoid position. Our findings may suggest the presence of intermetatarsal instability, which could limit the power of DCO in HV correction for more severe deformities and provide a mechanism for HV recurrence. Level of Evidence: Level IV, retrospective case series.